From centralized to distributed public service media: An analysis of market and public value-driven arguments. (1st June 2015) - Raats, Tim; Donders, Karen
In recent years, various regulators and advisory bodies have advocated for distributed public service models or at least explored its validity. This article aims to analyse the arguments for stepping away from centralized to distributed PSM systems. It questions whether proposals for distributed offers envisage distributed PSM as a complement or as a replacement of existing PSM organizations, whether motives are based on market failure or public interest objectives, how these underlying motives are transposed into specific policy plans and finally, to what extent they fit within a longer term strengthening of national media ecosystems or mainly serve to realize budget cuts and meet specific demands of private competitors. Findings are based on a literature study and an analysis of Flanders, United Kingdom, New Zealand and the Netherlands, in which debates on distributed PSM are recent or ongoing. The article argues that the efficiency and contestable funding arguments that underpin the advocacy for distributed public service are based on ideological market failure beliefs, similar to the ideological choice for centralized public service media. Debates on distributed models often go hand in hand with a desire to limit public service provision, or, a pragmatic stance of politicians seeking to please more than one player in the media market. An ecosystem logic that truly matches market with public interest objectives might therefore deserve a more fundamental exploration.